2014
DOI: 10.1136/oemed-2014-102362.282
|View full text |Cite
|
Sign up to set email alerts
|

0237 Psychosocial Impacts of a Contaminated Needlestick Injury or Blood and Body Fluid Exposure in Health Care Workers

Abstract: Method Fifty workers from two yacht factories participated, including 23 FRP laminators and 27 non-FRP workers. Pre-shift colour confusion index (CCI) was measured on the first workday of a week by using Lanthony Desaturated Panel D-15d. Concentrations of volatile organic compounds related to FRP laminating were collected by a stainless canister, and then analysed using a GC/MS. Cumulative working hours for FRP laminating was obtained from daily administrative records of the companies. Logistic regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Healthcare workers sustaining a sharps injury should be assessed and appropriate expert help provided for their psychological wellbeing (Ongete and Duffy, 2018). Owing to the psychological impact that sharps injuries can have on healthcare workers, Wu et al (2014) suggested that follow-up interventions should include psychosocial support, but the evidence suggests that this is not always happening. Only 61% (Royal College of Nursing, 2009) and 69% (Kable et al, 2011) of nurses were offered adequate support and counselling services post-sharps injury, a similar conclusion to the da Cunha Januário et al ( 2017) study which reported a lack of follow-up care for employees following a sharps exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare workers sustaining a sharps injury should be assessed and appropriate expert help provided for their psychological wellbeing (Ongete and Duffy, 2018). Owing to the psychological impact that sharps injuries can have on healthcare workers, Wu et al (2014) suggested that follow-up interventions should include psychosocial support, but the evidence suggests that this is not always happening. Only 61% (Royal College of Nursing, 2009) and 69% (Kable et al, 2011) of nurses were offered adequate support and counselling services post-sharps injury, a similar conclusion to the da Cunha Januário et al ( 2017) study which reported a lack of follow-up care for employees following a sharps exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Gershon et al (2000) stated that following their sharps injury, some healthcare workers were disappointed by the lack of follow-up such as counselling or coordination with their facility. Similarly, Wu et al (2014) reported a theme of 'disappointment on the working environment' to describe a lack of support for healthcare workers and the feeling of being isolated and helpless after a sharps injury.…”
Section: Discussionmentioning
confidence: 99%